2017
DOI: 10.18632/oncotarget.20085
|View full text |Cite
|
Sign up to set email alerts
|

Immunology repertoire study of pulmonary sarcoidosis T cells in CD4+, CD8+ PBMC and tissue

Abstract: Sarcoidosis is a systemic granulomatous disorder highly related with immune response. The diversity and stability of the immune system could be measured by hypervariable complementarity-determining region 3 (CDR3) segments of the T cell receptor (TCR). Here we used a combination of multiplex PCR and next-generation sequencing to conduct a good quality analysis of the T-cell receptor BV complementarity-determining region 3 (TCR BV CDR3) gene in peripheral blood mononuclear cells (PBMCs) from 7 sarcoidosis patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Sarcoidosis is a complex granulomatous disorder which is strongly related to immune response; however, its pathogenesis is still not completely understood. The immunological background of this disease involves the accumulation of activated macrophages and T-lymphocytes in affected organs, most commonly in the lung [101,102]. There is no information that epigenetic changes in monocytes could be associated with sarcoidosis, however both, occupational, environmental and infectious agents are involved in the development of this disorder [29].…”
Section: Chronic Inflammatory Disordersmentioning
confidence: 99%
“…Sarcoidosis is a complex granulomatous disorder which is strongly related to immune response; however, its pathogenesis is still not completely understood. The immunological background of this disease involves the accumulation of activated macrophages and T-lymphocytes in affected organs, most commonly in the lung [101,102]. There is no information that epigenetic changes in monocytes could be associated with sarcoidosis, however both, occupational, environmental and infectious agents are involved in the development of this disorder [29].…”
Section: Chronic Inflammatory Disordersmentioning
confidence: 99%
“…Previous work suggested that CD4 T cells play a role in sarcoidosis (Drent et al, 2021). For example, lungs in sarcoidosis contain an expansion of T cell clones, consistent with an antigen-driven inflammatory response (Fu et al, 2017;Silver et al, 1996;Trentin et al, 1997). Furthermore, Lofgren's syndrome, a subtype of sarcoidosis characterized by fever, erythema nodosa, arthritis, and hilar lymphadenopathy, is genetically linked to the MHC class II allele HLA-DRB1*03:01 (Grunewald and Eklund, 2009) and is associated with shared T cell receptor (TCR) sequences in bronchoalveolar lavage fluids across individuals (Greaves et al, 2021;Grunewald et al, 1994;Mitchell et al, 2017), suggesting a shared pathogenic antigen that is recognized by CD4 T cells.…”
Section: Introductionmentioning
confidence: 95%
“…Innovative experimental methods, such as microarrays utilizing extensive gene data, could offer fresh perspectives on possible pathogenic processes and related therapies for sarcoidosis [11,12]. Several sarcoidosis genomic studies have been carried out in various biosamples such as whole blood [13], peripheral blood mononuclear cells (PBMC) [12], bronchoalveolar lavage (BAL) cells [14], lung [15,16], and lymph nodes [17]. However, there are only a few studies investigating whether the gene expression of PBMC or whole blood, some of which is presumed to tra c to and from diseased tissues, was consistent with the tissue array results [18].…”
Section: Introductionmentioning
confidence: 99%